Endoscopic Ultrasound in Pancreatology: Focus on Inflammatory Diseases and Interventions - Vitali, Francesco; Zundler, Sebastian; Jesper, Daniel; Strobel, Deike; Wildner, Dane; De Pretis, Nicoló; Frulloni, Luca; Crinó, Stefano Francesco; Neurath, Markus (Visceral Medicine, 2023)
Background: Endoscopic ultrasound (EUS) is a main tool in pancreatology for both diagnosis and therapy. It allows minimally invasive differentiation of various diseases, with a minimal degree of inflammation or anatomic variations. EUS also enables interventional direct access to the pancreatic parenchyma and the retroperitoneal space, the pancreatic duct, the pancreatic masses, cysts, vascular structures for diagnostic and therapeutic purposes. Summary: This review aimed to summarize the new developments of EUS in the field of pancreatology, with special interest on inflammation and interventions. EUS enables way to perform pseudocyst drainage, necrosectomy, transenteral drainage and transenteric access of the main pancreatic duct, or the direct visualization or therapy of vascular structures adjacent to the pancreas. Key Messages: EUS has a deep impact on pancreatology, and the development of new diagnostic and interventional approaches to the retroperitoneal space and the pancreas has increased in the last years exponentially, allowing minimal invasive diagnostics and therapy and avoiding surgery and percutaneous therapy.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Endoscopic ultrasound; Endoscopic ultrasound-guided biopsy; Endoscopic ultrasound-guided drainage; Pancreatic cancer; Pancreatitis